Stress and rhythm in the Nigerian accent of English - Inyang M. Udofot (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
This paper undertakes the investigation of the disposition to stress of Nigerian users of English and the nature of Spoken Nigerian English rhythm. The subjects of the study are sixty Nigerians of varied socio-economic, educational and ethnolinguistic backgrounds and a native (British) English speaker whose productions from reading a passage and speaking freely for three minutes on a common topic were analysed perceptually, statistically and acoustically using the Wilcoxon Matched Pairs Signed Ranks Test, the Analysis of Variance (ANOVA) and the Fast Fourrier Transform (FFT) routine in the SignalyzeO software with a Performa 450 computer. The study identifies three varieties of Spoken Nigerian English characterized by their disposition to stress and speech rhythm: the Nonstandard, the Standard and the Sophisticated Varieties which are individually different but collectively similar yet different from Standard British English represented by the control's performance. The common performance features include a preponderance of stressed syllables and a tendency to have more or less even syllable durations and longer utterance durations than the native speaker. These features which are traceable to non-reduction of vowels in unstressed positions tend to characterise the Nigerian accent of English.